Announcement of Retraction - Annie Meredith (Science of Law, 2021)
The editorial board announced this article has been retracted on May 26, 2025 If you have any further question, please contact us at: info@legal-science.com Title: The Construct of Sex Work in France: A Qualitative Analysis of the Development of a Sex Work Policy Authors Eric Theiler: Swiss International Law School (SiLS), Basel, Switzerland Louis Vieillard: Paris Dauphine University, Paris, France Science of Law ISSN: 2995-8717 Volume and Number: Vol. 1, 2021 Pages: 1-6 DOI: https://doi.org/10.55284/sol.v2021i1.71